Connections Between Febrile Infection-Related Epilepsy Syndrome and Autoimmune Encephalitis. A Case Report of a Child With New Anti-neuronal Antibodies - Basso, Martina; Gastaldi, Matteo; Leonardi, Valeria; Izzo, Giana; Olivotto, Sara; Ferrario, Stefania; Veggiotti, Pierangelo; Franciotta, Diego; Bova, Stefania M. (Frontiers in Pediatrics, 2022)
Acute encephalitis and febrile infection-related epilepsy syndrome (FIRES) are debilitating neurological disorders. It is increasingly accepted that FIRES should be considered an autoinflammation-mediated epileptic encephalopathy, but the debate about its etiopathogenesis is still very much open. Despite showing a considerable overlap with encephalitis, it continues to be regarded as a distinct entity. We describe the case of a previously healthy 5-year-old child who, following a fever, developed acute encephalopathy, status epilepticus, neurological, neuropsychological and psychiatric manifestations, and claustrum involvement on MRI. At symptom onset, his clinical and instrumental data met the diagnostic criteria for both FIRES and acute encephalitis. He received benzodiazepines, levetiracetam, phenytoin, phenobarbital, thiopental and first-line immunotherapy for acute inflammatory encephalopathy (intravenous methylprednisolone and immunoglobulins), without substantial improvement. Following the detection of anti-neuronal antibodies through immunohistochemistry performed on rat brain slices, he received therapeutic plasma exchange (TPE). His neurological and behavioral conditions improved drastically and his antibody titer fell sharply from the first to the last course of PE. Claustrum abnormalities on MRI disappeared. The patient’s long-term outcome is favorable. At 13 months after discharge, he experienced a focal seizure and carbamazepine was started, achieving seizure control. At 10 years of age, he is still on carbamazepine, with well-controlled seizures, focal EEG abnormalities, and an otherwise normal neurological and cognitive profile and normal MRI. This case strengthens the view that FIRES might constitute the initial clinical presentation of a CNS inflammatory disease that could have, among multiple distinct etiologies, an autoimmune cause. Immunological and specific second- or third-level investigations including immunohistochemistry should be included in the diagnostic work up of patients with FIRES-like phenotypes. PE could be effective in this subset of patients, protecting them from long-term neurological sequelae.